EFEKTIFITAS EKSTRAK SERAI (Cymbopogon nardus) SEBAGAI INSEKTISIDA ALAMI DALAM MENGENDALIKAN SEMUT HITAM (Dolichoderus thoracicus) SECARA PENYEMPROTAN - LPPM Al-Insyirah (STIKes Al-Insyirah Pekanbaru, 2016)
The ant is the third home bug after mosquito and cockroach in tropical area. Black ant Dolichoderus thoracicus) is liquidated by synthetic insectiside which contain chemical compound. It is often generate asphyxiate, alergic on human, and negative impact for environment. The alternative way to extinguish bugs is using organic insectiside that made from plants such as Serai (Cymbopogon nardus). It has essential oil that contain citronella, citronellol, and geraniol. The aim of this studi were 1) to find out LD50 activity of several concentration from Serai extract on liquidating black ant (Dolichoderus thoracicus); 2) to determine the most efective concentration of Serai extract to eliminate black ant. The experiment design was a complete random design which consisted of 6 treatments – each treatment consisted of 20 ants - and 4 times of repetition. The Serai extract concentrations that used in this study were 25%, 50%, 75%, and 100%. The results showed that all concentration could kill black ants less than 5 minutes. After that, the concentration was lowered into 1%’ 2%, 3%, 4%, 5%, 10%, 15%, and 20%. One Way ANOVA showed that p < 0,05. It concluded that 5% Serai extract was the most efective concentraion to eliminate 50% of black ants.